Visi Orientalisme Hoesein Djajadiningrat Dalam Ilmu Pengetahuan Dan Pemajuan Identitas Kebudayaan (1911-1960) - Mohammad Refi Omar Ar Razy; Kunto Sofianto; Gani Ahmad Jaelani (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2022)
This paper aims to elaborate on the thoughts carried out by Hoesein Djajadiningrat during the colonial and post-colonial periods in the period 1911-1960. Hoesein Djajadiningrat studied in the Netherlands. His studies include oriental literature. He studied the east a lot from a western perspective, therefore Hoesein can be said to be an orientalist. So the approach in this paper uses the framework of orientalism. In simple terms, orientalism is a point of view in studying various aspects of the east from a western perspective. Usually, the orientalists are identical to westerners studying the east, but Hoesein, an easterner who received a western education, then studied the east from western perspective. Hoesein studied a lot about history (science) and cultural identity. He puts the west in terms of historical sources or cultural ideas as an explanation of local sources or ideas. The argues in this paper is that Hoesein Djajadiningrat's thinking is a prototype of thought that is commonly found in Indonesia in the early twentieth century. The method in this writing uses the historical method which consists of heuristics, criticism, interpretation, and historiography. This paper attempts to analyse, first, the pioneers of critical historiography in Indonesia. Second, the promotion of knowledge about cultural identity. Third, the change in post-colonial thinking. The findings in this paper are that Hoesein greatly contributed to science and the promotion of cultural identity during the colonial and post-colonial periods